PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAP HASIL BELAJAR PEKERJAAN DASAR OTOMOTIF SISWA SMK COKROAMINOTO KOTAMOBAGU - Fernando Fernando farses jamco; Hendrik Sumarauw; Davidsen Mapaliey; Lenie Ratag (Pendidikan Teknik Mesin, 2021)
ABSTRACT Education comes from the word learn which means to train and shape someone to be better. Education is important for every human being for the provision of advancing the level of welfare. This study aims to determine the effect of cooperative learning type make a match students of SMK COKROAMINOTO KOTAMUBAGU. The method in this research is pretest-posttest experimental class. The number of respondents in this study was 27 students who were selected using a total sampling technique. The results of data analysis using the normality statistical test of the Test whit a level of trust (α = 0.05) obtained a probability value = 0.000. From the results of statistical tests, it can be concluded that there is a significant effect of cooperative learning type make a match for students of SMK COKROAMINOTO KOTAMUBAGU. Keywords: Cooperative learning model make a match type